Prognostic significance of pretherapeutic body mass index in surgically treated oral squamous cell carcinoma - Richter, Maximilian; Doll, Christian; Mrosk, Friedrich; Hofmann, Elena; Koerdt, Steffen; Heiland, Max; Neumann, Konrad; Jöhrens, Korinna; Raguse, Jan-Dirk (Frontiers in Oncology, 2025)
ObjectiveAdditional prognostic factors in patients with early-stage oral squamous cell carcinoma (OSCC) may optimize disease staging by identifying patients with high-risk constellations and facilitating risk-stratified therapies that lead to improved treatment outcome. Body mass index (BMI) is an established tool that is routinely recorded in everyday clinical practice and has demonstrated prognostic relevance in various other diseases. However, sufficient evidence regarding its impact in OSCC is lacking. The aim of this study is to evaluate the prognostic significance of pretherapeutic BMI in surgically treated OSCC patients.Materials and methodsThis retrospective analysis included all patients with primary OSCC who underwent surgical therapy with or without the need for adjuvant therapy at Charité – Universitätsmedizin Berlin over a seven-year period. BMI was categorized based on the World Health Organization classification and correlated with clinical outcome. Overall survival (OS) and recurrence-free survival (RFS) were examined using Kaplan-Meier curves, Cox regression analysis, and log-rank test. The hazard ratios (HR) are presented together with 95% confidence intervals (CI).ResultsA total of 394 patients (male: 257 (65.2%), female: 137 (34.8%)) with a mean age of 60.0 years were included. Of these, 25 (6.3%) met the criteria for underweight, 195 (49.2%) for normal weight, 121 (30.6%) for overweight and 55 (13.9%) for obesity. Underweight patients showed a significantly lower mean OS of 46.0 months (CI: 30.9-61.2 months) and RFS of 36.5 months (CI: 24.4-48.6 months) compared to all other BMI categories. In the multivariate Cox regression for OS, a reduced risk was observed for both normal-weight (HR: 0.32 CI: 0.11-0.90, p=0.031) and overweight patients (HR: 0.17 CI: 0.05-0.59, p=0.005) relative to those who were underweight. Regarding RFS, overweight patients demonstrated a significantly reduced risk compared to underweight individuals (HR: 0.28 CI: 0.09-0.89, p=0.031).ConclusionOur results underscore the prognostic significance of pretherapeutic BMI as an independent risk factor in OSCC, particularly highlighting the need for intensified preoperative management in underweight patients due to their compromised outcomes.